The Five personality Traits Dome College Instructors of the University of Baghdad - Shaker, Sarab (Journal of Physical Education, 2011)
The world is interests in education to its great importance in the development of any country. Education can fire the potential energy and develop creative abilities in individuals such as college instructors. An instructor is the center of the leaning process and students are affected by personality traits whether good or bad. The problem of the research lies in diagnosing the weaknesses and strengths in college instructors’ personalities. The aim of the study is to identify the differences among personality traits in some college instructors in the university of the research is that there are significant statistical differences among personality traits in some college instructors in the University in the University of Baghdad . The subjects of the study were (69) college instructor taken from most colleges in the university of Baghdad, The researcher concluded that instructors from the colleges of physical education, pharmacy, education for women all share conscience, openness harmony which are all positive indicators of psychological health . He also concluded that there are no differences in personality traits between instructors of the college of pharmacy and the college of education for women. The researcher recommended using personality traits measurement for measuring the five major personality traits. He also recommended improving personality traits and limiting negative traits. Finally he recommended making similar researches on larger subjects from different colleges